Controlling Factors of the Spatial‐Temporal Fluctuations in Evapotranspiration Along an Elevation Gradient Across Humid Montane Ecosystems. Issue 1 (3rd January 2023) - Hu, Zhaoyong; Sun, Shouqin; Sun, Xiangyang; Lin, Shan; Song, Chunlin; Wang, Genxu
Abstract: Diverse meteorological and vegetation conditions at different elevations and years lead to varied contributions of evapotranspiration (ET) to water yield in montane areas. However, how physical and biological factors affect interannual and elevational ET fluctuations in energy‐limited montane ecosystems remains unclear. Therefore, we quantified the spatial‐temporal patterns of ET and separated physical and biological controls on ET fluctuations using 5‐year (2015–2019) eddy‐covariance data and perturbation analysis on Mount Gongga, Southwest China. Coefficients of variations of annual ET were 0.85%–4.33%, suggesting the remarkable interannual consistencies of ET in all studied zones. In forest zones, decreased precipitation ( P ) contributed more than 85% of ET reduction in the severe dry year, while the decreased vapor pressure deficit and available energy accounted for 88%, 78%, and 87% of transpiration reductions in broadleaf forest, broadleaf and coniferous forest and coniferous forest, respectively, in the wet year. In shrubland, the positive influence from biological factors (41.37 mm) surpassed the negative impact from physical conditions (−16.46 mm), resulting in an increase in ET in the wet year. Mean annual ET was highest at 2, 200 m a.s.l., 15.04% higher than that at 3, 996 m a.s.l. From perturbation analysis, elevational ET fluctuations were smaller in low‐elevation (12.31 mm) and middle‐elevation (−31.18 mm) zones than that in high‐elevation zone (−99.86 mm). Large elevational ET reduction in high‐elevation zone mainly resulted from decreased P and leaf area index. In humid montane areas, although ET is predicted to increase, how interannual and elevational ET respond to climate changes should be considered separately. Key Points: Remarkable interannual consistencies of evapotranspiration (ET) were found across humid montane ecosystems Interannual ET changes are more sensitive to precipitation reduction than precipitation increase in humid forest ecosystems Reductions in precipitation and leaf area index drive the decreased ET in the high‐elevation zone